Bifid mandibular condyle: A case report - Hadir Ghorbel; Raja Chebbi; Hanen Benkhalifa; Touhami Ben Alaya; Monia Dhidah (Radiology Case Reports)
Bifid mandibular condyle is an uncommon anatomical variation characterized by the division of the mandibular condyle into 2 or more lobes. In this paper, we present a case of unilateral bifid mandibular condyle in a 26-year-old male patient with no history of trauma. The patient presented with various joint noises prompting further investigations. The radiographic examinations showed an atypical mandibular condyle shape with 2 distinct mediolateral lobes. This case sheds light on the importance of thorough clinical and radiographic assessments in identifying such rare anatomical variations.